EFIKASI DAN KUALITAS HIDUP PASIEN SPASME HEMIFASIAL DENGAN SUNTIKAN TOKSIN BOTULINUM TIPE A - Yanni*, Paulus Anam Ong**, Suryani Gunadharma** (NEURONA, 2010)
INTRODUCTION HEMIFACIAL SPASM IS CHARACTERIZED BY INVOLUNTARY TONIC OR CLONIC MUSCLE CONTRACTION INNERVATED BY IPSILATERAL FACIAL NERVE IT CAN DISTURB PATIENTS QUALITY OF LIFE BOTULINUM TOXIN TYPE A INJECTION IS SAFE EFFECTIVE AND YIELDS IMPROVEMENT OF PATIENTS QUALITY OF LIFE